Performance and the partial. Issue 2 (1st December 2019) - Blades, Hetty
AbstractIn this article, I reflect on my experience of two performance works: Still Life (2018) by Hamish Macpherson and Papier mutliforme et Papier Comestible (2018) by Emilie Gallier, both of which cultivate partial experiences for the spectator. I consider how the partial nature of these works raise questions about what it means to access a choreographic work and rely on new ways of thinking about how we experience and analyse performance.